2016
DOI: 10.5539/ies.v9n5p28
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Support and Assertiveness as a Predictor of Candidates Psychological Counselors’ Psychological Well-Being

Abstract: In this research, to what extent the variables of perceived social support (family, friends and special people) and assertiveness predicted the psychological well-being levels of candidate psychological counselors. The research group of this study included totally randomly selected 308 candidate psychological counselors including 174 females (56.5%) and 134 males (43.5%) studying at Erzincan University, Faculty of Education, Psychological Counseling and Guidance Department in 2015-2016 academic year. The age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 36 publications
0
13
0
6
Order By: Relevance
“…The studies on determining the psychological well-being levels of the individuals have been carried out, on the one hand, and the variables affecting the psychological well-being of the individuals have been investigated, on the other. In this sense, it was noticed when the studies were reviewed that the variable of psychological well-being was correlated with the variables such as age, gender, academic success, level of education and marital status (Cenkseven, 2004;Khumalo et al, 2012), self-confidence (Sandhu, Singh, Tung and Kundra, 2012), physical health (Shields and Price, 2005), and social support (Ateş, 2016a;Du, Li, Chi, Zhao and Zhao, 2015;Karademas, 2006).…”
Section: Findings Discussion and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies on determining the psychological well-being levels of the individuals have been carried out, on the one hand, and the variables affecting the psychological well-being of the individuals have been investigated, on the other. In this sense, it was noticed when the studies were reviewed that the variable of psychological well-being was correlated with the variables such as age, gender, academic success, level of education and marital status (Cenkseven, 2004;Khumalo et al, 2012), self-confidence (Sandhu, Singh, Tung and Kundra, 2012), physical health (Shields and Price, 2005), and social support (Ateş, 2016a;Du, Li, Chi, Zhao and Zhao, 2015;Karademas, 2006).…”
Section: Findings Discussion and Resultsmentioning
confidence: 99%
“…Bir taraftan bireylerin psikolojik iyi oluş düzeylerini belirlemeye yönelik çalışmalar yapılırken diğer taraftan bireylerin psikolojik iyi oluşlarını etkileyen değişkenler araştırılmaya çalışılmıştır. Bu bağlamda yapılan çalışmalar incelendiğinde psikolojik iyi oluş değişkeninin kişilik özellikleri (Kokko, Tolvanen & Pulkkinen, 2013), yaş, cinsiyet akademik başarı, eğitim düzeyi ve evli olma, (Cenkseven, 2004;Khumalo, Temane & Wissing, 2012), öz güven (Sandhu, Singh, Tung & Kundra, 2012), fiziksel sağlık (Shields & Price, 2005), sosyal destek (Ateş, 2016a;Du, Li, Chi, Zhao & Zhao, 2015;Karademas, 2006), ve yalnızlık (Çeçen & Cenkseven, 2007) gibi değişkenlerle bağlantılı olduğu görülmüştür. Bu çalışmalardan da anlaşılacağı gibi bireylerin psikolojik iyi oluşları ile ilişkili veya bireylerin psikolojik iyi oluşlarını etkileyen birçok değişken vardır.…”
Section: Sonuç Tartışma Ve öNerilerunclassified
“…And, in their study on university students' assertiveness levels, Haladin, Ibrahim, & Rajab (2013) found a positive and linear relationship between students' assertiveness levels and communication skills. In his study that examined the relationships between assertiveness levels and social support perceptions and emotional well-beings of the teacher candidates attending to Psychological Counseling and Guidance Department, Ateş (2016) found that there was a positive and linear relationship between teacher candidates' assertiveness levels and emotional well-beings.…”
Section: Discussionmentioning
confidence: 99%
“…Öğretmen adaylarının lisans eğitimleri sırasında, kendi kararlarını alabilmeleri, sorumluluklarını yerine getirebilmeleri, problemlere etkili çözüm yolları bulabilmeleri beklenir. Bütün bunlardan yola çıkılarak öğretmen adaylarının güvengen davranışlara sahip olmaları gerektiği söylenebilir (Ateş, 2016). Ayrıca öğretmen adaylarının güvengenlik düzeylerinin yüksek olması, ileriki meslek yaşantılarında kişilerarası olumlu ilişkiler kurmalarına da katkı sağlayabilir.…”
Section: Sonuç Ve Tartışmaunclassified
“…Lack of social support has been implicated as a risk factor for depression in various conditions [9][10][11][12]. Various instruments currently exist for the measurement/assessment of social support.…”
Section: Introductionmentioning
confidence: 99%